Physicochemical Studies and Anticancer Potency of Ruthenium η(6)-p-Cymene Complexes Containing Antibacterial Quinolones - Kljun, Jakob (American Chemical Society, 2011)
[Image: see text] With the aim of exploring the anticancer properties of organometallic compounds with bioactive ligands, Ru(arene) compounds of the antibacterial quinolones nalidixic acid (2) and cinoxacin (3) were synthesized, and their physicochemical properties were compared to those of chlorido(η(6)-p-cymene)(ofloxacinato-κ(2)O,O)ruthenium(II) (1). All compounds undergo a rapid ligand exchange reaction from chlorido to aqua species. 2 and 3 are significantly more stable than 1 and undergo minor conversion to an unreactive [(cym)Ru(μ-OH)(3)Ru(cym)](+) species (cym = η(6)-p-cymene). In the presence of human serum albumin 1−3 form adducts with this transport protein within 20 min of incubation. With guanosine 5′-monophosphate (5′-GMP; as a simple model for reactions with DNA) very rapid reactions yielding adducts via its N7 atom were observed, illustrating that DNA is a possible target for this compound class. A moderate capacity of inhibiting tumor cell proliferation in vitro was observed for 1 in CH1 ovarian cancer cells, whereas 2 and 3 turned out to be inactive.